Synthesis, Characterization, Antibacterial Activity, and Potential Water Filter Application of Copper Oxide/Zeolite Composite - Kamila, Elfa Aida; Abidin, Zaenal; Arief, Irma Isnafia; Trivadila, Trivadila (Makara Journal of Science, 2023)
Detection of E. coli bacteria in water samples can indicate the presence of other bacterial contamination in feces. Bacterial contamination can be treated with antibiotics, but excessive use of antibiotics leads to the emergence of multiresistant bacteria. Therefore, alternative antibacterial agents must be explored. Copper ion/zeolite composite has been widely studied as an antibacterial agent. However, the released copper ions accumulate in water and are toxic to humans; this can be prevented by converting copper ions into copper oxides (CuO and Cu2O). In this study, copper oxide/zeolite composite is synthesized and characterized using the heating method, followed by evaluation of its effect, antibacterial activity, and potential application as a water filter. The results showed that heat treatment and combination of zeolite with copper did not change the composition of zeolite, rather impurities were reduced from natural zeolites. Antibacterial activity test against E. coli showed that the copper oxide/zeolite composite possessed good antibacterial activity and exhibited better potential as a water filter compared with copper/zeolite. The copper ion released from the synthesized materials was under 2 mg/L, indicating that it is safe for use provided the minimum contact between the sample and water for less than 20 min or 50–60 min.